2010
DOI: 10.1371/journal.pone.0014168
|View full text |Cite
|
Sign up to set email alerts
|

Selective Ablation of the Androgen Receptor in Mouse Sertoli Cells Affects Sertoli Cell Maturation, Barrier Formation and Cytoskeletal Development

Abstract: The observation that mice with a selective ablation of the androgen receptor (AR) in Sertoli cells (SC) (SCARKO mice) display a complete block in meiosis supports the contention that SC play a pivotal role in the control of germ cell development by androgens. To delineate the physiological and molecular mechanism responsible for this control, we compared tubular development in pubertal SCARKO mice and littermate controls. Particular attention was paid to differences in SC maturation, SC barrier formation and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
95
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(108 citation statements)
references
References 74 publications
6
95
0
Order By: Relevance
“…Furthermore, Sertoli cell-specific AR-KO mice displayed a defective BTB, which was associated with a reduced expression of claudin-11, ZO-1, occludin, and gelsolin but with a significantly enhanced expression of vimentin Willems et al, 2010a;Willems et al, 2010b). In addition, it was noted that Sertoli cell maturation and Sertoli cell polarization were also perturbed in these Sertoli cell-specific AR-KO mice, and that JAM-C (an apical ES marker that is also restricted to the apical ES) was shown to be significantly reduced (Willems et al, 2010a), illustrating that androgens are crucial to both apical and basal ES function. It is noteworthy that in AR flox(ex1-neo)/Y mice that had a partial defect in androgen sensitivity by carrying this floxed allele, a marked reduction in AR protein levels in different tissues including the testis was observed, as well as a defect in spermiogenesis, and these mice were infertile (Holdcraft and Braun, 2004).…”
Section: Tight Junction (Zonula Occludens) and Basal Ectoplasmic Specmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Sertoli cell-specific AR-KO mice displayed a defective BTB, which was associated with a reduced expression of claudin-11, ZO-1, occludin, and gelsolin but with a significantly enhanced expression of vimentin Willems et al, 2010a;Willems et al, 2010b). In addition, it was noted that Sertoli cell maturation and Sertoli cell polarization were also perturbed in these Sertoli cell-specific AR-KO mice, and that JAM-C (an apical ES marker that is also restricted to the apical ES) was shown to be significantly reduced (Willems et al, 2010a), illustrating that androgens are crucial to both apical and basal ES function. It is noteworthy that in AR flox(ex1-neo)/Y mice that had a partial defect in androgen sensitivity by carrying this floxed allele, a marked reduction in AR protein levels in different tissues including the testis was observed, as well as a defect in spermiogenesis, and these mice were infertile (Holdcraft and Braun, 2004).…”
Section: Tight Junction (Zonula Occludens) and Basal Ectoplasmic Specmentioning
confidence: 99%
“…For instance, it was shown that Sertoli cell-selective KO of AR in mice led to infertility manifested by meiotic arrest (Chang et al, 2004;De Gendt et al, 2004). Furthermore, Sertoli cell-specific AR-KO mice displayed a defective BTB, which was associated with a reduced expression of claudin-11, ZO-1, occludin, and gelsolin but with a significantly enhanced expression of vimentin Willems et al, 2010a;Willems et al, 2010b). In addition, it was noted that Sertoli cell maturation and Sertoli cell polarization were also perturbed in these Sertoli cell-specific AR-KO mice, and that JAM-C (an apical ES marker that is also restricted to the apical ES) was shown to be significantly reduced (Willems et al, 2010a), illustrating that androgens are crucial to both apical and basal ES function.…”
Section: Tight Junction (Zonula Occludens) and Basal Ectoplasmic Specmentioning
confidence: 99%
“…The biological repertoire describes ADHD as a neurological pathology and encourages its medication. English-written newspapers reporting scientific studies about ADHD almost exclusively support this repertoire (Gonon, Bézard, Boraud, 2011; Gonon, Konsman, Cohen, & Boraud, 2012). The psychosocial repertoire put forward inadequate parenting practices and social problems such as poor school systems, excessive TV exposure or high level of premature birth.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the quantitative threshold for detection of differential gene expression is generally higher for a microarray assay than for other methods. Studies of mice have also demonstrated the difficulties involved in modelling expression of testis steroids and their respective receptors during development (Willems et al, 2010).…”
Section: Discussionmentioning
confidence: 99%